Histórias do tio damião (1942-1951), by lourenco filho: An interpretation of brazil through children’s literature - Bertoletti, Estela Natalina Mantovani; Mortatti, Maria Do Rosário Longo [UNESP] (My University, 2018)
Brazilian educator Manuel Bergstrom Lourenco Filho (1897-1970) dedicated himself to a range of activities with national and international repercussion. Despite of the importance of his work and his concern with education in accordance with the principles of the educational renovation movement as well as with the political debate surrounding the modernization of the nation, especially from the 1930s onward, his production as a writer of children’s literature remained overlooked. Aiming to understand this facet of this educator’s work, the Serie Historias do Tio Damiao (1942-1951) is analyzed. It can be concluded that, by means of these books, Lourenco Filho taught an interpretation of Brazil to the children of the time, as well as a way of writing and editing texts and teaching through children’s literature, to adults of that time and beyond.
Keywords: Brasil; History of children’s literature; History of education; Modernization; XXth Century